CONDITIONERS OF DEMOCRATIC MANAGEMENT IN PUBLIC BASIC EDUCATION SCHOOLS - Folha De Araújo Oliveira, Mirian (Revista Gênero e Interdisciplinaridade, 2024)
This article is the result of a Doctoral Thesis in education whose object of study was to analyze institutional evaluation as a mechanism that enhances democratic management, investigating resonances of this relationship in public basic education schools. One of the paths was the identification of factors that have acted as conditions for democratic management. One of the conditions for the democratic management of public schools concerns management reforms, implemented in Brazil in recent decades, influenced by the neoliberal model of public administration. The second condition refers to the formation of educational policy discourse, which has been influenced by global and international networks in the process of formulating national policies, especially multilateral agencies that offer sponsorship for the implementation of certain national policies. A bibliographical research pointed out similar difficulties in different regions of Brazil regarding the limitations of implementing Democratic Management, highlighting the need to break with clientelistic and authoritarian management practices.